2003
DOI: 10.1017/s0003581500077684
|View full text |Cite
|
Sign up to set email alerts
|

The Economy of Dürrnberg-Bei-Hallein: An Iron Age Salt-mining Centre in the Austrian Alps

Abstract: RM) (continued) THE ANTIQUARIES JOURNALFor the first time in English, we present a summary of the international programme of excavation work carried out between 1990 and 2001 in and around the Iron Age salt-mining complex of the Diirrnberg region, south of Salzburg. First we describe the results of excavation in the prehistoric adits, and of work to locate and survey associated settlements. This is followed by a series of specialist reports embracing floral and faunal remains, palaeodiet and parasitology, leat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
(4 reference statements)
0
18
0
Order By: Relevance
“…P. anisum represents a newly introduced food plant north of the Alps, where climatic conditions allowed its local cultivation. Roman findings of P. anisum are rare north of the Alps, but macro remains were found in the Iron Age salt mining site of Dürrenberg-bei-Hallein in Austria (Stöllner et al 2003), and a pollen grain was identified in a Roman well in Weisweiler, Germany (Meurers-Balke 1989).…”
Section: Discussionmentioning
confidence: 99%
“…P. anisum represents a newly introduced food plant north of the Alps, where climatic conditions allowed its local cultivation. Roman findings of P. anisum are rare north of the Alps, but macro remains were found in the Iron Age salt mining site of Dürrenberg-bei-Hallein in Austria (Stöllner et al 2003), and a pollen grain was identified in a Roman well in Weisweiler, Germany (Meurers-Balke 1989).…”
Section: Discussionmentioning
confidence: 99%
“…1) for more than 3,000 years (Stöllner 2003; Grabner et al 2007). The mines and their surroundings are well described: Altaussee, Austria (Proisl 2003; Gawlick et al 2007; Hofer and Klade 2010); Berchtesgaden, Germany (Pichler 1963; Kellerbauer 1996; Braun 1998); Bad Dürrnberg, Austria (Plöchinger 1990, 1996; Gawlick and Lein 2000); Hall in Tirol, Austria (Schmidegg 1951; Spötl 1988d, 1989b); Bad Ischl, Austria (Mayrhofer 1955; Medwenitsch 1957); Hallstatt, Austria (Schauberger 1931, 1949; Spötl 1987; Habermüller 2005; Gawlick and Schlagintweit 2006; Suzuki and Gawlick 2009).…”
Section: Geological Settingmentioning
confidence: 99%
“…Though the massive rock salt mines of continental Europe were often run by the state during later periods, the earliest shafts were often created in periods that preceded the development of the state in a region (Alexianu et al 2011 ;Barth 1982 ;Boenke 2005 ;Megaw et al 2000 ;Stöllner 2003a ) . Centralized administration by the state or other authority is therefore not a necessary prerequisite to large-scale mining-Andean rock salt miners could have created an extensive, complex tunnel system without being organized by Inca, Wari, or Moche of fi cials.…”
Section: Salt Mining Common Resources and State Control In The Ancimentioning
confidence: 99%